2021
DOI: 10.1007/s11356-021-14620-z
|View full text |Cite
|
Sign up to set email alerts
|

Soil moisture responses under different vegetation types to winter rainfall events in a humid karst region

Abstract: Humid karst ecosystems are fragile, with precipitation being the main source of soil moist ure recharge. The process of soil moisture recharge and usage varies by vegetation type. To analyze the dynamics of soil moisture under different vegetation types during rainfall events, we continuousl y monitored soil moisture in arable land, grassland, shrub, and forest areas at 10-minute intervals fro m November 6, 2019, to January 6, 2020.The arable land was used as a control group. Soil moistur e under the different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 44 publications
(37 reference statements)
0
7
0
Order By: Relevance
“…The actual evapotranspiration was calculated by MODIS ground net evapotranspiration products. Soil moisture affects vegetation growth and hydrological processes, and its change will reflect the water conservation capacity of the basin (Yan et al, 2021; Zhou et al, 2022), which was calculated using the water balance method (Table 3, Formulas 6 and 7). It is worth noting that vegetation interception will eventually be consumed in the form of evapotranspiration; therefore, vegetation interception has already been included in the actual evapotranspiration in MODIS.…”
Section: Methodsmentioning
confidence: 99%
“…The actual evapotranspiration was calculated by MODIS ground net evapotranspiration products. Soil moisture affects vegetation growth and hydrological processes, and its change will reflect the water conservation capacity of the basin (Yan et al, 2021; Zhou et al, 2022), which was calculated using the water balance method (Table 3, Formulas 6 and 7). It is worth noting that vegetation interception will eventually be consumed in the form of evapotranspiration; therefore, vegetation interception has already been included in the actual evapotranspiration in MODIS.…”
Section: Methodsmentioning
confidence: 99%
“…Heavy rains showed the highest mean and maximum wetting front velocity (WFV), which accelerated the movement of soil water within the entire soil profile (Tables 3, 4). However, a continuous input of high-intensity rainfall may surpass the maximum rate of soil permeability and limit the soil water infiltration in the shallow layer (Yan et al, 2021), resulting in the shortest duration and the slowest permeating velocity of the 10-cm depth (Tables 3 and 4). Compared with heavy rains, intermediate rains (Group II) showed the shallowest RD (Figure 3) but the shortest response time (RT) and the fastest WFV of the 10-cm SM (Tables 3, 4).…”
Section: Effect Of Rainfall On Soil Moisture Dynamicsmentioning
confidence: 99%
“…The karst areas of Southwest China are typically characterized by high spatial heterogeneity [60,61], the soil moisture is primarily regionally varied, and its influencing factors are complex and diverse [17][18][19]. Climate change and human activities are two dominating factors affecting soil moisture temporal variation trends, but most studies have focused on small scales [9][10][11][12], such as plot, slope, and small watershed scales, which are unsuitable for illustrating the soil moisture trends and their influencing factors regionally. Overall, the individual contributions of climate change and human activities to temporal variation trends of regional soil moisture remain uncertain [13][14][15][16].…”
Section: The Contributions and Implications Of This Studymentioning
confidence: 99%
“…Many scholars have studied the temporal variation trends of soil moisture and its influencing factors. For example, based on the "space series instead of time series" method, Zhou et al highlighted that the succession of grassland to shrub and woodland would decrease the soil moisture content, and the shrubland is characterized by a more robust soil water conservation capacity than other land types in dry seasons [9,10]. Fu et al found that the soil moisture content of natural forestland was higher than that of abandoned and sloping farmlands, and the artificial forestland exhibited the lowest soil moisture content [11].…”
Section: Introductionmentioning
confidence: 99%